Modeling methods for the design of 3D broadcloth composite parts - Aono, M.; Breen, D.E.; Wozny, M.J. (Computer aided design, 2001)
The airframes of certain aircraft (ie, Lear Fan 2100) are totally fabricated from composite materials. Composites consist of a reinforcing material suspended in a 'matrix' material (ie, epoxy resin) that bonds it to adjacent reinforcing materials. The 3 major composite forms are chopped fibre, unidirectional tape, and (bi-directional) broadcloth. Today's aircraft mostly employ broadcloth composites partly because they have an outstanding strength-to-weight ratio, and partly because their structural properties may be tailored to the expected load in different directions. Broadcloth has both vertical and horizontal (weft and warp) threads interwoven to form a sheet of material that can strongly resist stretching along thread directions, but can be deformed flexibly along the thread diagonal, thus allowing the cloth to be 'formed' into virtually any curved surface. This paper presents a number of modelling methods that may be used to automate the design of 3D broadcloth composite parts. It first describes a model (a Tchebychev net) which simulates the deformation of woven materials into a specific 3D shape. 2 algorithms are described for performing the actual fitting. The first algorithm simulates the fit by solving the Tchebychev net formula using a finite difference technique and the second algorithm simulates the fit by reducing the problem to a surface - surface intersection problem. In addition, 3 approaches to the problem of preventing anomalous events such as wrinkles and breaks that may occur during the fitting process are presented. (Abstract quotes from original text)